Analisis Keikutsertaan Investor Asing dalam Peningkatan Aktivitas Perdagangan Saham di Bursa Efek Jakarta - Widayat, Utoyo (Jurnal Ilmiah Ranggagading (JIR), 2006)
The purpose of this research is to know how much the contribution of foreign investors on shares trade activity in Jakarta Stock Exchange. In this research, the total value of buying and selling transaction by the foreign investors are analyzed and compared with the total value of transaction in Jakarta Stock Exchange during September 1997 up to December 2003 period. The result of this research concluded that the roles of foreign investors on share trade activity were more dominant than domestic investors. Foreign investors represented one of indicators that supported and influenced domestic investors to enlarge the activity of shares transaction in Jakarta Stock Exchange. Key words: Stock Exchange; Shares.